Pluralism In Terrace Housing Community Through Ethnic Garden - Said, Ismail (Penerbit UTM Press, 2001)
Cultural-ethnic landscape symbolizes the belief and cultural values of an ethnic group living in a community. The landscape is an expression of people’s idea and work, illustrating intrinsic understanding and relationshi p of people to their fellow beings and environment. Such landscape is significant to the human community development and more challenging to establish it in a multi-ethnic society such as terrace house neighborhood in Peninsular Malaysia than in homogenous society. This paper discusses the role of ethnic gardens created by terrace housing residents towards integration and sense of belonging to their living neighborhood. The making of the residential gardens by Malays, Chinese and Indians are influenced by both cultural values and functional needs. There are few similarities and differences in planting composition, plant selection and garden accessories that reflect the strength of ethnicity and yet allow sharing of garden produce and create a sense of place for the community. This pluralism can be seen as positive phenomena to harmonize multi-ethnic society living in terrace housing neighborhoods in Peninsular Malaysia.